ANALYSIS OF ASSERTIVE SPEECH ACTS IN MINISTER NADIEM MAKARIM'S FINAL SPEECH ON NATIONAL EDUCATION DAY - Rambe, Aisyah Arfani; April Yanti; Desi Ramadali Hutauruk (Universitas Mahaputra Muhammad Yamin, 2025)
This article analyzes assertive speech acts in Nadiem Makarim's last speech as Minister of Education, Culture, Research, and Technolog on education national day Using a pragmatic approach, this study identifies the types of assertive speech acts used and their functions in conveying messages to the audience. This study aims to to identify the types of assertive speech acts used and their communicative functions in the context of the speech and also to explore the use of assertive speech acts in Nadiem Makarim's speech to understand their communicative functions and effectiveness in a formal context. Using a descriptive qualitative approach, cpthis study examines the speech transcript to classify assertive speech acts based on their type and function, drawing on frameworks from pragmatics.